2020
DOI: 10.1097/pcc.0000000000002073
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Factors Associated With Hemorrhage During Pediatric Extracorporeal Membrane Oxygenation

Abstract: Objectives: To quantify and identify factors associated with bleeding events during pediatric extracorporeal membrane oxygenation. Design: Retrospective cohort study with primary outcome of bleeding days on extracorporeal membrane oxygenation. Setting: Single tertiary care children’s hospital. Subjects: One-hundred twenty-two children supported with extracorporea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 26 publications
4
16
1
Order By: Relevance
“…The association between vascular complications and mortality has not been fully established, some studies have not established the association between ALI and mortality, and there is a wide range of opinions about what factors affect mortality in ECMO patients. There is also a wide variety of literature with conflicting conclusions and no guideline conclusion or expert consensus [ 21 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The association between vascular complications and mortality has not been fully established, some studies have not established the association between ALI and mortality, and there is a wide range of opinions about what factors affect mortality in ECMO patients. There is also a wide variety of literature with conflicting conclusions and no guideline conclusion or expert consensus [ 21 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fifty-five percent of the patients were male with a median (IQR) age of 0 (0-2) years. The median (IQR) length of ECMO was 5 (2)(3)(4)(5)(6)(7)(8)(9) days with a hospital mortality rate of 34%. Platelets were transfused on 49% of ECMO days, plasma on 33% of ECMO days and cryoprecipitate on 17% of ECMO days.…”
Section: Interventions: Nonementioning
confidence: 99%
“…In a cohort of 514 children supported by ECMO at eight children's hospitals in the US, bleeding occurred in over 70% of patients and was independently associated with mortality ( 4 , 5 ). In addition, bleeding in children supported by ECMO has been associated with fewer ventilator-free days and hospital-free days ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, approximately 2-3% of all neonatal and pediatric patients undergoing cardiac surgery for congenital heart defect need post-surgical extracorporeal membrane oxygenation (ECMO) support [1]. There are various determination methods for insufficient tissue perfusion, such as measurement of lactate level, mixed venous oxygen saturation (ScVO2), blood pressure, urine output, use of regional near-infrared spectroscopy (NIRS), and inotrope requirement at any time point of ECMO therapy [2]. Nonetheless, the value of these means is quite limited in complex ECMO settings.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the value of these means is quite limited in complex ECMO settings. In addition, only a few previous studies showed that measurement of blood lactate clearance can be proportional to tissue oxygen demand and thus be a reliable prognostic predictor for outcomes [2,3]. High lactate values can predict occurrence of multiorgan failure and inadequate tissue perfusion [3][4][5].…”
Section: Introductionmentioning
confidence: 99%